The power of the 'objective' Bayesian unit-root test - Francis W. Ahking (The Open Economics Journal, 2009)
Some researchers, for example, Koop [1], and Sims [2], have advocated for Bayesian alternatives to unit-root testing over the classical approach using the augmented Dickey-Fuller test (ADF). This paper studies the power of what Koop [1] has called the Objective Bayesian approach to unit-root testing. Koop's objective Bayesian test is interesting in light of the call by Phillips [3, 4] for more objective Bayesian analysis of time series. We apply the objective Bayesian unit-root test to a study of long-run purchasing power parity (PPP) in the post-Bretton Woods era and also Monte Carlo simulations. Overall, contrary to the favorable simulation results obtained by Koop [1], our results suggest that the objective Bayesian test is biased in favor of trend-stationarity. We conclude that, at least for the objective Bayesian test, it is not better than the classical ADF approach in unit-root tests, and because of its bias, the objective priors suggested by Koop [1] is not appropriate, and we do not recommend its use.
Keywords: C11; C22; F31; 330; unit-root test; objective bayesian test; long-run PPP